Pemikiran Pendidikan Islam Muhammad Abduh dan Muhammad Iqbal - Normuslim Normuslim (Anterior Jurnal, 2013)
Muhammad Abduh and Muhammad Iqbal are two of the reformers of Islamic thought who are very popular in the East and even the West. Both are thinkers who have different typologies, although that does not mean that they are opposite, but they are complementary. Muhammad Abduh is a thinker who emphasizes changes in society at a macro level, whereas Muhammad Iqbal prioritizes natural self-change. The equation is that in general they both carry out reforms towards reformulating the Islamic religious doctrine in all lines of human life and placing reasoning (rationality) in an urgent place. Both try to integrate aspects of religiosity (religion) and aspects of rationality (philosophy) as a single truth.Education is one aspect of both thoughts which basically Abduh and Iqbal initiated an independent Islamic education system, not bound or dependent on a foreign (Western) education system, but able to absorb Western rationality and integrate it with an Islamic education system born of the local Islamic community .